On unitarizable modules over generalized Virasoro algebras - Mazorchuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We classify unitarizable modules with highest weight and unitarizable modules of an intermediate series over generalized Virasoro algebras.